GREEN MANAGEMENT IN HIGHER EDUCATION INSTITUTIONS: AN OPINIONATED REALITY OF ITS APPLICATION (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Green management is on the rise. With a shifted focus on environmental protection, it has become quite a buzzword lately. In fact, almost every business around the globe today is highly immersed in greening its establishment. To add to that, a range of past and recent research has repeatedly demonstrated the significant importance of green management within organizations. Except that green management comes with its own challenges. It is in no way as easy as it is put. The following study focuses on the reality and actual intensity of green management application in higher educational institutions. It primarily aims to examine the real expanse of green management practices in an educational institution based on the opinions of its students and teachers. Besides, it also analyses whether the opinions of the teachers and students differ and addresses the gaps, if any. As a part of this study, based on a well-structured questionnaire, a survey has been conducted amongst the students and teachers of a few recognisable universities in Jaipur, Rajasthan. The results of the study indicated that higher educational institutions are actively pursuing green management to a significant extent and that the opinions of both students and faculty members are very similar, which could be a positive foundation for maintaining a successful educational setting. However, the findings also revealed a considerable gap in meeting students’ environmental expectations, indicating the necessity for institutions to reassess and enhance their practices accordingly.